Skin Manifestations in Dengue Patients of a Tertiary Hospital during Dengue Epidemic in Kathmandu: A Retrospective Study - Seema Sitaula; Suraj Shrestha; Punam Mishra; Mamata Subba; Elisha Poddar (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: With a wide range of clinical manifestations and a drastic shift in epidemiology, dengue infection is a life-threatening condition. Studies of skin manifestations in dengue fever are scarce, and hence, it is prudent to explore the skin manifestations of dengue in Nepal for prompt diagnosis and to reduce associated complications.